Role of pharmacodiagnostic of CYP2C9 variants in the optimization of warfarin therapy in Malaysia: a 6-month follow-up study - Ngow, Harris Abdullah; Teh , Lay Kek; Langmia, I. M.; Lew, W. L.; Harun, R.; Ismail, R.; Salleh, Mohd Zaki (Informa Plc., 2008)
1. A retrospective study was conducted to explore the importance of CYP2C9 genotyping for the initiation and maintenance therapy of warfarin in clinical practice. A total of 191 patients on warfarin therapy in a local hospital were recruited after written informed consent. Their medical records were reviewed and no intervention of warfarin dose was performed. 2. A total of 5 ml of blood were taken from each subject for DNA extraction and identification of 1, 2, 3 and 4 CYP2C9 alleles, using a nested-allele-specific-multiplex-polymerase chain reaction (PCR). Half the patients were Malays and the remaining were Chinese. 3. Two genotypes were detected; 93.2% had CYP2C9 1/1 and 6.8% were CYP2C9 1/3. Warfarin doses were higher in patients with CYP2C91/1. Patients with the 1/3 genotype experienced a higher rate of serious and life-threatening bleeding; 15.4 versus 6.2 per 100 patients per 6 months. 4. The observation clearly highlights the inadequacy of the current dosing regimens and the need to move toward a more individualized approach to warfarin therapy. Prospective clinical studies are now being conducted to assess dosing algorithms that incorporate the contribution of the genotype to allow the individualization of warfarin dose.